استخدام الانترنت كأداة لتقديم الخدمات البنكية و أثره على العمل البنكي دراسة حالة البنوك الجزائرية - العطرة, أ.دغنوش (Recherches économiques et managériales; Vol. 18 (2015): RECHERCHES ÉCONOMIQUES ET MANAGÉRIALES (Décembre), 2015)
هدفت هذه الدّراسة إلى التعرف على "أثر استخدام شبكة الانترنت على العمل البنكي لدى البنوك الجزائرية  ولتحقيق هدف الدّراسة تمّ تطوير استبانة، و توزيعها على عينة الدراسة المكونة من ثمانية بنوك العاملة في ولاية الجزائر و التي تمثل الادارات الرئيسية للبنوك دون الفروع. و تم توزيع الاستبانة على مجموع الاطارات العاملة في هذه البنوك المكونة من كل المديرين و نوابهم و رؤساء الدوائر و رؤساء المصالح، ومن أبرز نتائج الدراسة تمثلت في أن أغلب البنوك الجزائرية تقدم خدمات مصرفية عبر شبكة الانترنت و أنه هناك أثر لاستخدام الانترنت على العمل البنكي فتقديم الخدمات البنكية عبر الانترنت يؤدي الى تخفيض  التكاليف التشغيلية المتمثلة في تكاليف الدعاية و الاعلان و تكاليف تقديم الخدمة مباشرة من مبنى البنك مما يدل على فعالية الانترنت كبديل عن الطرق التقليدية . كما يؤدي الى زيادة الايرادات و سرعة انجاز المعاملات و دقتها و تلبية حاجيات العملاء . ABSTRACT     This study aimed to identify the "impact of the use of the Internet on the bank to work for Algerian banks To achieve the objective of the study was the development of a questionnaire, and ensure validity and reliability then distributed to a random sample of 96 framework factor in the Algerian banks that are the study population and the estimated number eight 8 banks, and were excluded (10) questionnaires for non-suitability tests for statistical analysis, and thus the number of questionnaires recoverable statistical analysis operations (80) questionnaire, and highlighted the results of the study was that most Algerian banks offer banking services via the Internet and that there is a trace to use online banking work Providing banking services via the Internet leads to a reduction of advertising costs and advertising operational costs and the costs of providing the service directly from the bank building which shows the effectiveness of the Internet as an alternative to traditional methods. also lead to increased revenues and the speed of completion of transactions and accuracy and meet the needs of customers..